GLOBAL FINANCIAL TECHNOLOGIES (FINTECH) AND THEIR TRANSFORMATIONAL IMPACT ON THE BANKING SYSTEM - ESHQORAYEV , JAVOHIR (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the impact of global financial technologies—specifically Blockchain, decentralized finance systems (DeFi), and Central Bank Digital Currencies (CBDC)—on the banking system within the IMRAD framework. The paper examines the transformational influence of modern FinTech innovations on traditional banking services, their role in expanding financial inclusion, and the associated issues of security and regulatory challenges. The study also highlights the prospects of implementing such technologies in developing countries like Uzbekistan.